IMPLEMENTATION OF THE RECOGNITION AND RESPECT OF THE DAYAK IBAN SEMUNYING CUSTOMARY LAW COMMUNITY IN HUMAN RIGHTS AND SDGS - Christmas, Sandy Kurnia; Muhajir, Ichsan; Wicaksono, Imam (Lembaga Penelitian dan Pengabdian Masyarakat, 2020)
Weak implementation of the recognition and respect for Indigenous Peoples of Iban Semunying be problems related to their discriminatory practices in running a government policy. Why is the implementation of the recognition and respect for the Indigenous People of  Dayak Iban Semunying still weak and how the principles of human rights and the Sustainable Development Goals are the two issues raised in this article. In this study it aims to find out what are the things that form the basis of the weak protection of indigenous peoples. The results of this study are expected to provide insight into the protection of the rights of indigenous peoples with a perspective of sustainable development goals.